Studies on other phases of matter binary granular matter and microwave plasma - Arciaga, Marko E. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
Studies on two other phases of matter - granular matter and plasma - are reported in this work. In the first study, the existence of enhanced heap stability as a result of the mixing of granular materials is demonstrated. The setup consists of a rectangular container, filled with a binary mixture of granular matter up to some height h, that is rapidly opened at one wall to allow repose angle formation. Characterization was done via information gathered from the usual Langmuir probe measurements for electron temperature and density. The source makes a resonant surface with its repulsive double hexapole magnetic configuration providing an additional longitudinal confinement near the walls midway between the two hexapoles. Magnetic field maps are presented for varying double hexapole distances. Power delivery for various settings is also presented.